The Optics of the Pre-Raphaelite Keats - Jukić, Tatjana (2003)
The early Pre-Raphaelite fascination with John Keats demonstrates, inter alia, a special value of Italianicity for Victorian culture (to borrow a term coined by Roland Barthes). In my article I focus on the assumption that the Pre-Raphaelite paintings from Keats utilize his poetry in the same way in which Keats’ s poetry utilizes Italy. While Keats speaks of sensuality and violence from within a cordon sanitaire constructed out of an imaginary Italy, the Pre-Raphaelites use Keats’ s poetry as a cordon sanitaire within their own – visual – discourse, to show yet withhold the representation of excessive violence and desire.
Projekt MZOS
ENG